Land markets, employment, and resource use in the peri-urban green zones of Maputo, Mozambique : a case study of land market rigidities and institutional constraints to economic growth - Roth, Michael J.; Boucher, Steve; Francisco, Antonio (Land Tenure Center, University of Wisconsin--Madison, 1995)
Beginning in January 1991, the U.S. Agency for International Development funded a series of studies on land, employment, and financial markets in the peri-urban areas of Maputo. Beginning in September 1991, a land-market survey involving 121 households and 162 plots of land was administered in two peri-urban green zones of Maputo-districts 4 and 6. Households were queried about their land-settlement histories, mode of land acquisition, terms and conditions of transfer, land rights, size of holdings, perceptions of tenure security, land-use practices, commercial input use, hired labor, agricultural sales and revenues, nonfarm employment and earnings, and general demographic characteristics. The present study reports findings from the land-market survey along with numerous other interviews with producers, buyers and sellers of land, local authorities, and district and national officials in Maputo and its surrounding peri-urban green zones. Section 1 is introductory while section 2 covers the legal foundation of land tenure and describes the various authorities and agencies responsible for setting and enforcing land policy in the peri-urban zone. Section 3 explains the research design and sampling frame used to select households and landholdings for the study, choice of strata, survey instruments, research questions, and data limitations. Section 4 provides a statistical profile of the household economy while section 5 examines processes of land settlement, land acquisition, types and sources of land dispute, and registration benefits. In section 6, economic and political factors are linked with land prices to explain the determination of "reservation" and "offer" prices of land and to evaluate the influence of market factors and Possible asymmetries in information and bargaining position on land-price perceptions.
xxxi, 122 p., Executive summary also in Portuguese.
Keywords: Land titles Mozambique Maputo; Urban agriculture Mozambique Maputo; Land tenure Mozambique Maputo; Land use, Urban Mozambique Maputo; Greenbelts Mozambique Maputo; Land markets Mozambique; Land tenure, Urban Mozambique